Evaluation of iron , magnesium and selenium in sera of acute and chronic myelgeneous leukemia Iraqi patients (Journal of the College of Basic Education, 2022)
The present study performed on acute myelgeneous leukemia (AML) and chronic myelgeneous leukemia (CML) attending kadhmiya teaching hospital in addition to 20 healthy individual as control group . The elements Fe , Mg and Se were evaluated in the sera of all above individuals using atomic absorption spectrophotometry .The results revealed a non significant difference in Fe concentration among all studied groups, while a significant decrease in Mg and Se levels in both patients groups compared to control were found , on other hand no significant difference in Mg and Se levels in sera of AML and CML was notice. A conclusion is that trace element abnormalities occur in both patients groups compared to control